Resveratrol reduces muscle atrophy and stress pathway activation in a combined disuse-hypoxia-mouse model - Khan, Aziz Ahmad; Sadozai, Sajid Khan; Ali, Fawad; Khan, Nemat; Qaisar, Rizwan (Frontiers in Pharmacology, 2026)
IntroductionMechanical disuse and hypoxia synergistically worsen muscle atrophy by activating apoptosis, necroptosis, and ER stress pathways. While resveratrol, a natural polyphenol, has shown protective effects in isolated disuse or hypoxia models, its efficacy under combined conditions remains unclear.MethodsMale C57BL/6J mice (4 months old) were assigned to ground control or hindlimb unloading (HU) groups under normoxia (21% O2) or hypoxia (15% O2) and treated daily with placebo or resveratrol (20 or 40 mg/kg) for two weeks. Muscle mass, grip strength, cling time, and gene expression of apoptotic, necroptotic, and ER stress markers were assessed.ResultsHU-hypoxia significantly reduced muscle mass and function, with upregulation of stress-related genes. Resveratrol showed dose-dependent protection: 20 mg/kg modestly reduced atrophy, while 40 mg/kg nearly preserved muscle mass and strength to control levels under both normoxic and hypoxic conditions. To our knowledge, this is the first study to demonstrate protective effects of resveratrol in a combined HU and hypoxia model of muscle atrophy, accompanied by modulation of apoptosis, necroptosis and ER stress related gene expression.ConclusionThese results suggest that resveratrol may decrease muscle degradation in fast twitch dominant muscles under combined disuse and hypoxia. However, these results are restricted to gastrocnemius muscle in mice, and further investigations in slow twitch muscles and clinical models are required before clinical relevance can be confirmed. These findings support its potential as a therapeutic agent for muscle loss in clinical and spaceflight settings, warranting further translational research.